FAKTOR-FAKTOR YANG MEMPENGARUHI PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA SISWI KELAS XI DI SMK PELITA INSANI KOTA PRABUMULIH - Dwi Saputri MS; Precelia Fransiska (LPPM STIKes Mitra Adiguna, 2024)
Breast self-examination (BSE) is an early detection effort to prevent breast cancer. This BSE activity is carried out by someone to examine and find out any changes in their breasts. The aim of the research is to find out the factors that influence breast self-examination (BSE) in class Cross Sectional. The population of this study were female students in class The research instrument is a questionnaire. The results of the research based on univariate analysis showed that of the 55 respondents there were 41 respondents (74.5%) who had BSE examinations and 14 respondents (25.5%) who had not carried out BSE examinations, there were 37 people (67.3%) who had knowledge good and 18 people (32.7%) who had poor knowledge, there were 9 people (16.4%) who had a family history of breast cancer and 46 people (83.6%) who had no family history of breast cancer, there were 45 people (81.8%) had a normal age at menarche and 10 people (18.2%) had an abnormal age at menarche. From the bivariate analysis there is a significant relationship between knowledge and BSE examination with a P value of 0.000 < ? 0.05, there is a significant relationship between family history and BSE examination with a P value of 0.000 < 0.05. There is a significant relationship between age at menarche and BSE examination with a P value of 0.000 < 0.05. It is hoped that this BSE examination will be used as part of the health education that must be given to obstetrics clinics so that they can disseminate information about early detection of ca mammae disease.